Plan de marketing para la Microempresa Smartmove del Cantón Otavalo. - Maigua Sosa, Luis Diego (2015)
Otavalo is known worldwide thanks to its culture, customs, and wonderful scenery, due to these factors the influx of tourists is evident and significant, offering traditional tourist services such as photography, hiking, horseback riding, dining, visit the Square ponchos, however it is necessary to propose alternatives that contribute to its further development. The company SmartMove aware that innovation is a must for competitive firms, raises to add value to hiking and sightseeing in the city of Otavalo, by designing tourist routes planned to be flown aboard a Segway vehicle named applying technology, nature, tourism and historical knowledge to routes raised (dairy route, route and route Hummingbird Square ponchos). Considering that marketing is a tool to retain and attract new markets, the proposal: marketing plan for micro Smartmove Canton Otavalo allowing potentiate their product, reaching new domestic and foreign markets through advocacy, diversification of supply and a sideshow like the Segway, two-wheeler novel and striking movements reading, regulates the speed, care and physical integrity easy to use. By changing the idea of a normal tour in the city of Otavalo, and adapting the service that the company Smartmove, the vision of a normal tour will be another, will be a dynamic, innovative and adventurous journey.